the first three terms of a series of which the nth term is 2n+1.​

the first three terms of a series of which the nth term is 2n+1.​

0 thoughts on “the first three terms of a series of which the nth term is 2n+1.​”

  1. Answer:

    3, 5, 7

    Step-by-step explanation:

    n = 1, 2, 3 into the nth term rule

    a₁ = 2(1)+1=2+1=3

    a2=2(2)+1=4+1=5

    a3 = 2(3)+1=6+1=7

    Reply
  2. Answer:

    3, 5, 7

    Step-by-step explanation:

    Substitute n = 1, 2, 3 into the nth term rule

    a₁ = 2(1) + 1 = 2 + 1 = 3

    a₂ = 2(2) + 1 = 4 + 1 = 5

    a₃ = 2(3) + 1 = 6 + 1 = 7

    Reply

Leave a Comment